2020
DOI: 10.1097/j.pain.0000000000001894
|View full text |Cite
|
Sign up to set email alerts
|

Premonitory symptoms in glyceryl trinitrate triggered migraine attacks: a case-control study

Abstract: Spontaneous and pharmacologically provoked migraine attacks are frequently preceded by nonheadache symptoms called premonitory symptoms. Here, we systematically evaluated premonitory symptoms in migraine patients and healthy controls after glyceryl trinitrate (GTN) infusion. In women with migraine without aura (n = 34) and age-matched female controls (n = 24), we conducted systematically a semistructured interview assessing 21 possible premonitory symptoms every 15 minutes in the 5 hours after GTN infusion (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Despite their similarity with spontaneous attacks, induced attacks need to be referred to as ‘migraine-like headaches’, because by nature they cannot fulfill the criteria for migraine without aura, which require the attack to be spontaneous and last (untreated) at least 4 h ( Headache Classification Committee of the International Headache Society (IHS), 2018 ). Therefore, similarly to previously published provocation studies, we used the following criteria for defining migraine-like attacks, fulfilling either: 1) moderate to severe headache (VRS ≥ 4) fulfilling ICHD-3 criteria C and D for migraine without aura; or 2) headache described as mimicking the patients' usual migraine attack and treated with acute migraine medication ( Arngrim et al, 2016 , Onderwater et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their similarity with spontaneous attacks, induced attacks need to be referred to as ‘migraine-like headaches’, because by nature they cannot fulfill the criteria for migraine without aura, which require the attack to be spontaneous and last (untreated) at least 4 h ( Headache Classification Committee of the International Headache Society (IHS), 2018 ). Therefore, similarly to previously published provocation studies, we used the following criteria for defining migraine-like attacks, fulfilling either: 1) moderate to severe headache (VRS ≥ 4) fulfilling ICHD-3 criteria C and D for migraine without aura; or 2) headache described as mimicking the patients' usual migraine attack and treated with acute migraine medication ( Arngrim et al, 2016 , Onderwater et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Glyceryl trinitrate provocation studies have only rarely been able to provoke aura symptoms and generally provokes migraine-like attacks in over eighty percent of migraine without patients ( Ashina et al, 2013 ). In both GTN provoked and spontaneous attacks patients may experience premonitory symptoms in the preictal phase, and using neuroimaging techniques activation of hypothalamus, occipital cortex and brainstem has been demonstrated ( Ferrari et al, 2015 , Maniyar et al, 2014a , Maniyar et al, 2014b , Onderwater et al, 2020 , Schulte and May, 2016 ; van Oosterhout et al, 2021 , Weiller et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
“…The premonitory phase has been studied in some detail in the literature over the years, in both adults and children, with a variety of study designs and patient populations ( Blau, 1980 ; Drummond and Lance, 1984 ; Waelkens, 1985 ; Rasmussen and Olesen, 1992 ; Russell et al, 1996 ; Giffin et al, 2003 ; Kelman, 2004 ; Quintela et al, 2006 ; Schoonman et al, 2006 ; Cuvellier et al, 2009 ; Guo et al, 2016 ; Karsan et al, 2016 , 2020b ; Laurell et al, 2016 ; Jacobs and Pakalnis, 2019 ; Onderwater et al, 2020 ; Wang et al, 2021 ). While some studies have looked at prevalence and the ability of these symptoms to predict impending headache, others have focused on phenotype.…”
Section: Non-painful Symptoms In Migraine (Ictally During Any Phase or Interictally)mentioning
confidence: 99%
“…Provocation studies have found that glyceryl trinitrate induces migraine attacks that are preceded by premonitory symptoms, i.e. non-headache symptoms that occur within minutes to hours before the onset of headache in attacks with migraine without aura [ 22 , 23 ]. Premonitory symptoms are regarded as surrogate markers of activation within central nervous system structures, such as the hypothalamus [ 19 ].…”
Section: Lessons Learned and Outstanding Research Questionsmentioning
confidence: 99%